Adolescent Peer Support Profile at School - Muslikah Muslikah; DYP Sugiharto; Sugiyo Sugiyo; Anwar Sutoyo; Abdul Kholiq (Universitas Negeri Semarang, 2022)
Based on developmental tasks, adolescents have increased social interest in peers. This has an impact on mental health, so it needs to be analyzed in depth. This study aims to explore the profile of peer support in adolescents. The research approach is descriptive quantitative. The sample of this research is teenagers who study at the junior and senior high school level in Central Java which were selected randomly. The results show that on average, adolescents get peer support at a moderate level. The biggest aspect is support in obtaining awards while the lowest aspect is in terms of emotional support. This has implications for guidance and counseling services in schools in the future fostering the students to grow well.